Evaluation of salespeople by the purchasing function: implications for the evolving role of salespeople. Issue 4 (1st October 2020) - Paesbrugghe, Bert; Rangarajan, Deva; Hochstein, Bryan; Sharma, Arun
Abstract: As the focus on the effectiveness of salespeople has increased, we concentrate on the fact that selling involves broad sets of actors and investigate the approaches and behaviors of salespeople from the perspective of the purchasing agent to develop a deeper theoretical understanding of the effectiveness of salesperson strategies. Our focus is on the purchasing function that is increasingly involved in the buying process, and we examine a central research question—how does the purchasing function view salespeople's strategies and behaviors? We describe the results of in-depth interviews with 35 purchasing executives that focused on how the purchasing function views salespeople's strategies and behaviors. The findings suggest that salespeople, in general, do not focus enough on the needs of the purchasing function. Salespeople are not meeting the purchasing function needs, and purchase-centered sales strategies may need to be developed. These findings have theoretical and managerial implications and offer directions for future research in this area.